PENGARUH FASILITAS, HARGA DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN DI HANA HOTEL BATAM - Meilinda, Mia Audina; Ratnasari, Sri Rat Langgeng (Zona Manajerial: Program Studi Manajemen (S1), 2019)
Hotel firms began compelled to further strengthen the basis of the strategy with concepts such as customer focused or market oriented culture to still be able to access the market profitably and ensure sustainable growth. The purpose of this study is as follows: first to determine the effect the facility partially on customer satisfaction Hotel Batam. The second to determine the effect on the price of partially towards customer satisfaction Hotel Batam. Third to determine the effect Citra hotel partially towards customer satisfaction Hotel Batam. Fourth to determine the effect on the amenities, price and image simultaneously on customer satisfaction Hotel Batam. From result research and discussion on the Effect of amenities, price and image on customer satisfaction Hotel Batam then obtained the following conclusions: first that the variable facility has an influence on customer satisfaction in Hotel Batam. The second that the price variable has an influence on customer satisfaction in Hotel Batam. Third that the variable image has an influence on customer satisfaction in Hotel Batam. Fourth F count was 179.044 with Sig0,000 <Î±0,05 and the coefficient of influence or R2 of 0,868 or 86,6%. 86,6% means that the performance of the research is affected facilities, price and image. While the remaining 13,2% is influenced by other variables that are not the focus of this study. Thus these data suggest a significant means There is influence amenities, price and image simultaneously on Customer Satisfaction Hotel Batam.